FINANCIAL AND NON-FINANCIAL FACTORS INFLUENCING INTERNET FINANCIAL AND SUSTAINABILITY REPORTING (IFSR) IN INDONESIA STOCK EXCHANGE - Almilia, Luciana Spica (Journal of Indonesian Economy and Business, 2010)
Internet Financial and Sustainability Reporting (IFSR) is voluntary in nature. With noÂ specific regulations on IFSR, there is a disparity of IFSR practices among companies.Some companies disclose only partial financial statement using a low level of technology,Â while others disclose full sets of financial reports using sophistications of the web such asÂ multimedia and analytical tools. Sustainability (1999) addressed the benefits (globalÂ reach, immediacy, ease of updating, transparency, link ability, and interactivity) ofreporting social and environmental information on the website and thus the factors thatÂ affect decision of whether or not to use this communication medium. By placinginformation on the firmâs website, users can search, filter, retrieve, download, and evenÂ reconfigure such information at low cost in a timely fashion.The purpose of this study was to examine financial variables that affect InternetÂ Financial and Sustainability Reporting (IFSR) of listed in Indonesia Stock ExchangeÂ companies. The ordinal logistic regression used to examine variables that affect InternetÂ Financial and Sustainability Reporting (IFSR). The sample of this research is companiesÂ that listed in Indonesia Stock Exchange. The 203 observations were divided into threeÂ categories: 87 companies not providing financial and sustainability report in the internetÂ (No website), 62 companies providing financial and sustainability report in the internetÂ with low index (Low Index) and 54 companies providing financial and sustainability reportin the internet with high index (High Index). The result shows that firm size, majorityÂ shareholders, auditor size and industry type as a determinant factor of internet financialand sustainability-reporting index in Indonesia, whereas leverage and profitability notÂ statistically significant as determinant factors of internet financial and sustainabilityreporting index in Indonesia.Keywords: internet financial reporting, website, traditional financial reporting, internet,Â financial statement, voluntary disclosure.